1999
DOI: 10.1074/jbc.274.38.27105
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Phosphopantetheine Adenylyltransferase from Escherichia coli

Abstract: Phosphopantetheine adenylyltransferase (PPAT) catalyzes the penultimate step in coenzyme A (CoA) biosynthesis: the reversible adenylation of 4-phosphopantetheine yielding 3-dephospho-CoA and pyrophosphate. Wild-type PPAT from Escherichia coli was purified to homogeneity. N-terminal sequence analysis revealed that the enzyme is encoded by a gene designated kdtB, purported to encode a protein involved in lipopolysaccharide core biosynthesis. The gene, here renamed coaD, is found in a wide range of microorganisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
112
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 56 publications
3
112
0
Order By: Relevance
“…These two steps are carried out by a bifunctional polypeptide, phosphopantothenoylcysteine synthetase decarboxylase (denoted CoaBC, formally Dfp) (2). The last two steps are carried out by two separate enzymes, namely phosphopantetheine adenylyltransferase (CoaD) (3,4) followed by the addition of the 3Ј-ribose phosphate by dephospho-CoA kinase (CoaE) (5). E. coli is capable of de novo pantothenate biosynthesis (1) or can import pantothenate from the medium via a sodium-dependent active transport process (6)(7)(8).…”
mentioning
confidence: 99%
“…These two steps are carried out by a bifunctional polypeptide, phosphopantothenoylcysteine synthetase decarboxylase (denoted CoaBC, formally Dfp) (2). The last two steps are carried out by two separate enzymes, namely phosphopantetheine adenylyltransferase (CoaD) (3,4) followed by the addition of the 3Ј-ribose phosphate by dephospho-CoA kinase (CoaE) (5). E. coli is capable of de novo pantothenate biosynthesis (1) or can import pantothenate from the medium via a sodium-dependent active transport process (6)(7)(8).…”
mentioning
confidence: 99%
“…Geerlof et al (5) have shown that homologous overexpression of an enterobacterial coaD gene in E. coli led to the production of a protein containing a CoA molecule. The UV spectrum measured for His-tagged PAB0944 is reported in the inset of Fig.…”
Section: Fig 4 Reverse Ppat Activity Assaymentioning
confidence: 99%
“…Secondary structure predictions were obtained through the PSIpred v2.4 web-interfaced facilities 4 described by McGuffin et al (20) or through the IBPC consensus program. 5 Nuclear Magnetic Resonance Spectroscopy-Unlabeled PAB0944 sample was prepared at a concentration of 0.1 mM in a 10 mM KH 2 PO 4 / Na 2 HPO 4 buffer (pH 7.2), and 10% D 2 O. The sample was degassed, argon-saturated, and sealed before analysis.…”
Section: Chemicalmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3Ј-end of the cluster contains the waaA (CMP-Kdo:lipidA Kdo bifunctional transferase and waaE (glucosyltransferase) genes adjacent to core OS-unrelated genes coaD (phosphopantetheine adenylyltransferase) (29) and fpg (formamidopyrimidine-DNA glycosylase) (30). In the middle of the cluster, genes waaQ (ADP-L-glycero-␣-Dmanno-heptosepyranose transferase III), wamA (ADP-D-glycero-D-manno-heptopyranose transferase), wabG (UDP-GalA transferase), wabH-like (UDP-GlcNAc transferase), and wabN (LPS-GlcNAc deacetylase) were identified (Fig.…”
Section: P Mirabilis Wa Genementioning
confidence: 99%